Gestational diabetes and its correlation with maternal socio-demographic characteristics - Nask Jalal Jubrael; Shahla K Alalaf; Nazar Shabila; Salah Abubaker Ali (Zanco Journal of Medical Sciences, 2022)
Background and objective: Gestational diabetes mellitus is the most common metabolic disorder of pregnancy with increasing prevalence at epidemic rates. This study aimed to determine the prevalence of gestational diabetes mellitus and related risk factors in a sample of pregnant women in Erbil city.